2008
DOI: 10.1128/jb.01206-07
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Horizontally Acquired Genes by the Hha-YdgT Proteins in Salmonella enterica Serovar Typhimurium

Abstract: We describe a transcriptomic study of the effect of hha and ydgT mutations in Salmonella enterica serovar Typhimurium. A large number of genes showing altered expression are located in AT-rich horizontally acquired DNA sequences. Many of these genes have also been reported to be targets for H-NS. As Hha and YdgT interact with H-NS, our findings strongly suggest that Hha and/or YdgT must form complexes with H-NS when they silence these DNA regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 39 publications
3
68
0
Order By: Relevance
“…When activated within macrophages, the SsrB protein promotes transcription of SPI-2, possibly by counteracting the H-NS-and YdgT-mediated repression (7). Indeed, deletion of the ydgT gene attenuated Salmonella virulence in a mouse infection model, which may have resulted from the expression of SPI-2 genes with inappropriate timing (i.e., under repressing conditions) and/or at inappropriate levels under inducing conditions (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…When activated within macrophages, the SsrB protein promotes transcription of SPI-2, possibly by counteracting the H-NS-and YdgT-mediated repression (7). Indeed, deletion of the ydgT gene attenuated Salmonella virulence in a mouse infection model, which may have resulted from the expression of SPI-2 genes with inappropriate timing (i.e., under repressing conditions) and/or at inappropriate levels under inducing conditions (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a transcriptomic study has shown that Hha and its paralogue YdgH could be involved in the regulation of the rck operon (Vivero et al, 2008). Fig.…”
Section: Rck Regulationmentioning
confidence: 99%
“…At many loci, H-NS alone is insufficient for full transcriptional silencing, and members of the Hha/YdgT family of coregulatory proteins are also required (20,21). Hha and YdgT are small (8-kDa) protein paralogues that enhance repression at a subset of the H-NS regulon.…”
Section: The Bacterial Nucleoid-associated Proteins Hha and H-ns Joinmentioning
confidence: 99%